Strength and Durability Evaluation of Recycled Aggregate Concrete - Yehia, Sherif (2015)
This paper discusses the suitability of producing concrete with 100 % recycled aggregate to meet durability and strength requirements for different applications. Aggregate strength, gradation, absorption, specific gravity, shape and texture are some of the physical and mechanical characteristics that contribute to the strength and durability of concrete. In general, the quality of recycled aggregate depends on the loading and exposure conditions of the demolished structures. Therefore, the experimental program was focused on the evaluation of physical and mechanical properties of the recycled aggregate over a period of 6 months. In addition, concrete properties produced with fine and coarse recycled aggregate were evaluated. Several concrete mixes were prepared with 100 % recycled aggregates and the results were compared to that of a control mix. SEM was conducted to examine the microstructure of selected mixes. The results showed that concrete with acceptable strength and durability could be produced if high packing density is achieved.